Evaluation of selected aspects of influenza surveillance system and describing influenza surveillance data collected during 2014-2018 of district general hospital Matara, Sri Lanka - Samaraweera, Nayana Y. (International Journal of Advances in Medicine, 2022)
Background: Influenza is one of the diseases which have the pandemic potential. Influenza surveillance as part of the pandemic preparedness activities was initiated in Sri Lanka in 2005. This study would help in evaluating, strengthening influenza surveillance system of DGH Matara, and taking targeted preventive measures and contribute to more efficient resource allocation in the future. Methods: This was a cross sectional analytical study. Results: Case definitions for ILI and SARI used were consistent with the epidemiology unit Sri Lanka prescribed definitions. Though the site collected data on cases daily and sampled weekly, sampling technique was not random. Respiratory specimen collection, packaging, storage and transport were consistent with the guidelines of epidemiology Unit, Sri Lanka. Refrigerator temperature monitoring, analyzing surveillance data on site as well as supervisory visits made by central level were not satisfactory. No clear pattern of ILI and SARI was observed among different age groups during 2014-2018. Influenza viral activity was detected except for “untyped” from respiratory samples sent by DGH, Matara during 2014-2018. Pandemic preparedness by the site was not at optimal level. Conclusions: Representativeness of data obtained from respiratory specimen collection and data analyzing were not satisfactory. Temperature monitoring inside storage refrigerators of the site was not possible as no written records were available. Supervision from the central level was not satisfactory.